On the Incidence Energy of Some Toroidal Lattices. (1st September 2014) - Liu, Jia-Bao; Cao, Jinde; Xie, Jin
Abstract : The incidence energyI E ( G ), defined as the sum of the singular values of the incidence matrix ofG, is a much studied quantity with well known applications in chemical physics. In this paper, we derived the closed-form formulae expressing the incidence energy of the 3.12.12 lattice, triangular kagomé lattice, andS ( m, n ) lattice, respectively. Simultaneously, the explicit asymptotic values of the incidence energy in these lattices are obtained by utilizing the applications of analysis method with the help of software calculation.